The changes of the tubular epithelium phenotype in the contralateral kidney nephrons while developing unilateral ureteral obstruction: an experimental study - M. A. Akimenko; O. V. Voronova; T. S. Kolmakova (Вестник урологии, 2021)
Introduction. The high prevalence of renal diseases caused by urinary tract obstruction led to the need for experimental research of compensatory and pathological processes with kidney injury. It is also of relevance to study key mechanisms providing a compensatory function of the contralateral kidney for early diagnosis, treatment, and prognosis of obstructive renal diseases.Purpose of the study. To examine epithelial nephron cells phenotype dynamics changes in contralateral kidney using unilateral ureteral obstruction experimental model.Materials and methods. Model of unilateral ureteral obstruction was established using adult rabbits. The studies were carried out on days 7, 14 and 21 of complete obstruction of the left ureter. Immunophenotyping was performed on contralateral kidney tissue samples using epithelial (cytokeratin 7, E-cadherin) and mesenchymal (vimentin, α-smooth muscle actin) markers.Results. The contralateral kidney under additional load can maintain the morphological and functional characteristics of the nephron for a long time. The first transmogrify signs in the nephron epithelium phenotype were detected by day 21 as the diffuse appearance of mesenchymal marker vimentin with unaltered visualization of epithelial phenotype markers.Conclusion. The results obtained allow us to assume that the compensatory reserve of the contralateral kidney is gradually decreasing when the duration of the obstruction increases. Thus, the likelihood of developing negative disorders increases.